EFFECTIVE WAYS OF TEACHING ENGLISH TO SECONDARY SCHOOL LEARNERS - Rakhmonova , Dilshoda (Educational Research in Universal Sciences, 2023)
Teaching English to secondary school learners poses unique challenges due to the cognitive abilities and interests of adolescent students. This article explores effective instructional approaches and strategies for engaging secondary students in English language learning. Peer collaboration, project-based learning, integrating technology and authentic materials, giving regular feedback and focusing on real-world applications of English are discussed as impactful practices. The article highlights how these learner-centered techniques can boost motivation and achievement in English among secondary learners.